PENGARUH KINERJA, KOMPETENSI DAN DISIPLIN KERJA PEGAWAI TERHADAP KEPUASAN MASYARAKAT PADA KANTOR KECAMATAN KALIDERES - Resti Apriyanti (2022)
This research is a quantitative research that aims to test and prove the effect of performance, competence and work discipline on people's satisfaction partially and simultaneously. This study used a sample of 100 people who used the services of the Kalideres Sub-District Head Office with accidental sampling technique. In this study, data were obtained through a questionnaire which was measured using a Likert scale. The data analysis technique used is descriptive and inferential analysis using SmartPLS 3.0. The results of this study indicate that: 1) performance has a positive and significant effect on people's satisfaction; 2) competence has a positive and significant effect on community satisfaction; 3) work discipline has a negative and significant effect on people's satisfaction; 4) performance, competence and work discipline have a simultaneous effect on people's satisfaction. Keywords : Performance; Competence; Work Discipline; Community Satisfaction